Uncovering the Roots of Structural Poverty in East Java Province: An Analysis of Determinants - Shinta Rifianing Prasetya; Wiwin Priana Primandhana; Wirya Wardaya (International Journal of Economics, Business and Innovation Research, 2024)
Structural poverty is defined as a condition that occurs when a certain group of people experiences poverty because the social structure does not allow them to develop economically and take advantage of the sources of income that are actually available. East Java Province with the highest poverty rate in Indonesia is suspected to be related to the causes of structural poverty. The purpose of this study is to determine the determination of structural poverty in districts and cities in East Java Province in 2013-2022 by using poverty indicators that affect poverty levels, namely the Gender Development Index, Gini Ratio, and Life Expectancy Rate. This research method uses panel data regression analysis. The results of the analysis with the Random Effect Model model show that the Gender Development Index and Life Expectancy have a significant effect and have a negative relationship with poverty which shows that gender inequality and inequality in access to health have an effect on poverty in East Java.